2021
DOI: 10.3389/fphar.2021.675350
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferia galanga L.: Progresses in Phytochemistry, Pharmacology, Toxicology and Ethnomedicinal Uses

Abstract: K. galanga is an aromatic medicinal herb. It is locally to India and distributed in China, Myanmar, Indonesia, Malaysia, and Thailand. K. galanga is a Traditional Chinese Herb Medicine (TCHM), which has been applied to treat cold, dry cough, toothaches, rheumatism, hypertension and so on. In addition, it has been used widely as spices since its highly aromas. The aim of this review is to compile and update the current progresses of ethnomedicinal uses, phytochemistry, pharmacology and toxicology of K. galanga.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 78 publications
0
23
0
Order By: Relevance
“…Kaempferia galanga ( K. galanga ) is an aromatic herb grown mainly in tropical and subtropical Asia ( 19 ) and is used in the treatment of cold, dry cough, toothaches, rheumatism, hypertension, and so on ( 20 ). Modern pharmacological investigations have revealed that the extracts and natural products identified from K. galanga exhibited comprehensive bioactivities, including antitumor, antioxidant, anti-inflammatory, and other health effects ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kaempferia galanga ( K. galanga ) is an aromatic herb grown mainly in tropical and subtropical Asia ( 19 ) and is used in the treatment of cold, dry cough, toothaches, rheumatism, hypertension, and so on ( 20 ). Modern pharmacological investigations have revealed that the extracts and natural products identified from K. galanga exhibited comprehensive bioactivities, including antitumor, antioxidant, anti-inflammatory, and other health effects ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown to inhibit TNF‐ α ‐induced signaling transduction in L929 cells and attenuate ear inflammation in an acute mouse model. Kaempferol, extracted mainly from Kaempferol galanga L , is widely found in many edible plants and herbal medicines, [ 25 ] and is known for its anti‐inflammatory and anti‐oxidative effects. [ 26 ] Significantly, kaempferol has been shown to attenuate the severity of arthritis in a collagen‐induced arthritis (CIA) mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…It has shown various activities including anti-inflammatory, analgesic, and antioxidant effects, due to their secondary metabolites content. 12 , 13 K. galanga L. is easy to grow in Indonesia and other countries on the Asian continent. 14 The results of our preliminary study have identified the content of ethyl- p -methoxycinnamate (EPMC) and flavonoids in the ethanolic extract of K. galanga L. rhizome.…”
Section: Introductionmentioning
confidence: 99%
“… 15 We also have reported that the best percentage of yield and water, as well as the secondary metabolites content, was obtained from plants harvested in the rainy season. 16 The phytochemical screening of K. galanga L. rhizome indicated the presence of: kaempferol; 12 , 13 EPMC and ethyl cinnamate, that have showed anti-inflammatory and antinociceptive activity better than that of indomethacin as the COX inhibitor 17 and aspirin; 18 quinones and terpenes; 19 polyphenols and flavonoids. 15 It has been reported in a study that diarylheptanoids can be isolated from K. galanga and stated to have a potential effect for the treatment of diseases associated with inflammation.…”
Section: Introductionmentioning
confidence: 99%